(untitled) (مجلة المنصور, 2022)
As requirement engineering is considered to be the most important phase in software development process because of the high cost impact of repairing requirement phase errors, therefore web requirement engineering is known to be one of the most popular research areas today. By observing most of the conducted researches it can be concluded that they focus on the application of user experience from content, navigational and presentational point of view. UML (Unified Modeling Language) is a general purpose visual modeling language for specifying, constructing and documenting systems, which can be used in all major application domains and implementation platforms. In this paper a new dimension in the UML user experience modeling will be presented which represents the style factor or by other words the web theme. Every company, business or corporation has its own styling factors which are essential for the success of the institute’s mission, and therefore should be referred to as ‘requirements’. This new dimension will be translated into a new web style diagram with all the associated relationships and constrains. The web style diagram will enable the customer (institute requesting the web site or application) to ensure that the resulting web site or application will meet their style identity.